2020
DOI: 10.1016/j.jpainsymman.2020.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Patients' Perceived Difficulties Filling Opioid Prescriptions After Receiving Outpatient Supportive Care

Abstract: Context. Limited access to opioids for patients with cancer has been reported as a potential unintended consequence of recent regulations restricting opioid use and prescribing practices. To our knowledge, there are a limited number of peerreviewed studies that evaluate the perceived difficulties of the patients with cancer when filling their opioid prescription. To understand these difficulties, we surveyed patients receiving opioids in our outpatient supportive care center (SCC).Objectives. The primary objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…99,100 When provided a prescription for an opioid, patients with cancer consistently recount problems obtaining the medication, with one quarter describing perceived difficulties during interactions with pharmacy staff. 101 Some of these problems arise because of the complexities of medication dispensing in our current health care system. Is the drug available at the pharmacy, and if so, will insurance pay?…”
Section: Barriers To Opioid Accessmentioning
confidence: 99%
“…99,100 When provided a prescription for an opioid, patients with cancer consistently recount problems obtaining the medication, with one quarter describing perceived difficulties during interactions with pharmacy staff. 101 Some of these problems arise because of the complexities of medication dispensing in our current health care system. Is the drug available at the pharmacy, and if so, will insurance pay?…”
Section: Barriers To Opioid Accessmentioning
confidence: 99%
“…6 Since then, studies conducted in Massachusetts, Georgia, Texas, and the Midwest described patient-reported fears of addiction, difficulty filling opioid prescriptions, negative media coverage, and guilt. [7][8][9][10] A recent study of oncologists in western Pennsylvania, an area severely affected by the opioid crisis, described stigmatizing interactions between patients and clinicians, pharmacists, and society in general. 11 Exploring these concerns with patients directly will fill an important gap in this literature.…”
Section: Corresponding Author Original Contributionsmentioning
confidence: 99%
“…These recommendations include limits on daily dosing, the use of signed agreements, urine drug screening, medication-assisted therapy (MAT), prescription drug monitoring programs (PDMPs) monitoring, and prescribing rescue doses of naloxone 3 . The CDC guidelines specifically state that they are “not intended for patients undergoing active cancer treatment, palliative care, or end-of-life care.” This was reiterated in an additional statement published in 2019 after case reports of patients receiving cancer treatment being denied opioid prescriptions because of insurance company and pharmacy chain policies and restrictions based on the CDC guidelines 7-10 …”
Section: Clinical Practice Guideline Developmentmentioning
confidence: 99%
“…This was reiterated in an additional statement published in 2019 after case reports of patients receiving cancer treatment being denied opioid prescriptions because of insurance company and pharmacy chain policies and restrictions based on the CDC guidelines. [7][8][9][10] Cancer pain guidelines often fail to fully address how to approach care for patients who are deemed high risk for development of or have already been diagnosed with SUDs. 4,11 Many national and international organizations, including the American Society of Clinical Oncology, World Health Organization, The European Society for Medical Oncology, and the National Comprehensive Cancer Network (NCCN), have developed clinical practice guidelines specifically addressing the treatment of cancer-and treatmentrelated pain.…”
Section: Clinical Practice Guideline Developmentmentioning
confidence: 99%